Sharia-Based Financial Inclusion Strategies for the Economic Empowerment of the Poor: A Systematic Literature Review - Marlina Ekawaty; Moh Agus Nugroho (Talaa : Journal of Islamic Finance, 2025)
This study employs a Systematic Literature Review (SLR) approach to examine the role of Sharia-based financial inclusion in empowering the poor and fostering economic justice in Indonesia. The review analyzes eleven peer-reviewed studies published between 2020 and 2024, focusing on the implementation of Islamic financial instruments such as Sharia microfinance, zakat, Islamic cooperatives, and digital Islamic financial technology (fintech). The findings reveal that Sharia-based financial inclusion significantly contributes to poverty alleviation by increasing access to capital, promoting entrepreneurship, and improving financial literacy among marginalized groups. However, its effectiveness is often constrained by governance challenges, regulatory fragmentation, and inadequate digital infrastructure. The results underscore the importance of institutional collaboration, innovation in financial products, and inclusive regulatory frameworks. Integrating Islamic economic principles with national development strategies, along with enhanced financial literacy programs, is vital for achieving sustainable socio-economic outcomes. This study contributes to the literature by synthesizing recent findings on the strategic role of Sharia-compliant finance in promoting inclusive development and offers actionable insights for policymakers, practitioners, and Islamic financial institutions in designing more effective and ethical financial inclusion strategies.